Green Taxonomy Research: A Bibliometric Mapping of Sustainable Finance Development - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
The increasing urgency to address climate change and achieve sustainable development goals has accelerated the transformation of global financial systems toward more environmentally responsible practices. Green taxonomy has emerged as an important policy and financial instrument designed to classify sustainable economic activities, improve transparency, prevent greenwashing, and facilitate the allocation of capital toward environmentally beneficial projects. This study aims to examine the intellectual structure, research trends, and development patterns of green taxonomy research within the broader field of sustainable finance through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords associated with green taxonomy, sustainable finance, and green finance. The retrieved publications were analyzed using bibliometric techniques, including publication trend analysis, citation analysis, keyword co-occurrence mapping, density visualization, thematic evolution analysis, and collaboration network analysis using VOSviewer. The findings indicate that green taxonomy research has experienced significant growth, particularly following the emergence of sustainability regulations and climate-oriented financial frameworks. The analysis identifies sustainable finance, sustainable development, green finance, green bonds, climate finance, and EU taxonomy as the dominant research themes shaping the field. Furthermore, recent studies have increasingly focused on greenwashing prevention, sustainability reporting, transition finance, and the integration of taxonomy frameworks into financial decision-making processes. The collaboration analysis reveals that European countries, particularly Germany and other EU members, play a central role in advancing research, while emerging economies are gradually expanding their contributions. This study contributes to the sustainable finance literature by providing a comprehensive overview of the evolution of green taxonomy research and identifying future research directions related to regulatory implementation, climate risk management, and sustainable investment transformation.